Assessment of Cardiovascular Function in Childhood Leukemia Survivors: The Role of the Right Heart - Paola Muggeo; Pietro Scicchitano; Vito Michele Rosario Muggeo; Chiara Novielli; Paola Giordano; Marco Matteo Ciccone; Maria Felicia Faienza; Nicola Santoro (MDPI AG, 2022)
Childhood acute lymphoblastic leukemia (ALL) survivors who underwent chemotherapy with anthracyclines have an increased cardiovascular risk. The aim of the study was to evaluate left and right cardiac chamber performances and vascular endothelial function in childhood ALL survivors. Fifty-four ALL survivors and 37 healthy controls were enrolled. All patients underwent auxological evaluation, blood pressure measurements, biochemical parameters of endothelial dysfunction, flow-mediated dilatation (FMD) of the brachial artery, mean common carotid intima-media thickness (c-IMT), antero-posterior diameter of the infra-renal abdominal aorta (APAO), and echocardiographic assessment. The ALL subjects had significantly lower FMD (p = 0.0041), higher left (p = 0.0057) and right (p = 0.0021) echocardiographic/Doppler Tei index (the non-invasive index for combined systolic and diastolic ventricular function) as compared to controls. Tricuspid annular plane excursion (TAPSE) was 16.9 ± 1.2 mm vs. 24.5 ± 3.7 mm, p < 0.0001. Cumulative anthracycline doses were related to TAPSE (p < 0.001). The ALL survivors treated with anthracyclines demonstrated systo/diastolic alterations of the right ventricle and reduced endothelial function compared with healthy controls. The early recognition of subclinical cardiac and vascular impairment during follow up is of utmost importance for the cardiologist to implement strategies preventing overt cardiovascular disease considering the growing number of young adults cured after childhood ALL.